2014
DOI: 10.1002/jee.20032
|View full text |Cite
|
Sign up to set email alerts
|

First‐Year Students' Environmental Awareness and Understanding of Environmental Sustainability Through a Life Cycle Assessment Module

Abstract: Background Incorporating environmental sustainability (ES) into engineering education is vital to both individual engineering students' success and to the profession as a whole. This study explores attitudes, conceptions, and misconceptions about ES that students bring to the classroom. A promising framework of design-based research is applied to gauge how instructional innovation can impact student attitudes, conceptions, and misconceptions.Purpose Two questions guided this research: What knowledge and attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 38 publications
(46 reference statements)
0
29
0
Order By: Relevance
“…Furthermore, younger people are expected to have a greater level of environmental awareness (Stragham and Robberts, 1999), as age is an key factor affecting the tendency to be environmentally responsible and influencing environmental attitudes (Liobikiene and Juknys, 2016). Finally, although some studies exploring the impact of gender are inconclusive (Dietz et al, 1998;Han et al, 2011), there is evidence that women, with high levels of environmental awareness, have greater pro-environmental behavior compared to men (Weber et al, 2014).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Furthermore, younger people are expected to have a greater level of environmental awareness (Stragham and Robberts, 1999), as age is an key factor affecting the tendency to be environmentally responsible and influencing environmental attitudes (Liobikiene and Juknys, 2016). Finally, although some studies exploring the impact of gender are inconclusive (Dietz et al, 1998;Han et al, 2011), there is evidence that women, with high levels of environmental awareness, have greater pro-environmental behavior compared to men (Weber et al, 2014).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Despite the lack of research, existing studies have shown many benefits of using LCA in education. For instance, LCA can support scientific development [31], increase students understanding and awareness of environmental issues [32], motivate students [33], and increase interest toward science [34]. Several of the studies have also shown that LCA can help increase awareness and interest towards new career options [32,34].…”
Section: Life-cycle Assessment As a Context For Learningmentioning
confidence: 99%
“…One reason for low vocational relevance (c.f. [32,34]) in this study could be that the students only familiarized themselves with one career in detail. Though they were able to decide which career to familiarize themselves with, they may not have been able to relate to the chosen career because of many reasons, including outside factors, such as the personality of the expert they interviewed.…”
Section: Vocational Relevancementioning
confidence: 99%
“…This is in line with results obtained by Byrne et al (2013), who remarked that although there is a consensus about the importance of integrating sustainability and sustainable development into engineering curricula, little progress has been seen regarding an effective integration of these concepts (Allen et al, 2009). In turn, this delays the development of sustainable engineering skills (Desha et al, 2009 (Mulder, 2017;Weber et al,2014).…”
Section: Sustainability Lca and Carbon Footprint In Current Chemicalmentioning
confidence: 99%